The impact of divestitures on shareholder wealth: The DACH case - Nils Teschner; Herbert Paul (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The purpose of this research is to study the impact of divestitures on shareholder wealth. This study covers selloffs of publicly traded companies in Germany, Austria and Switzerland (DACH region) during the period 2002-2018. It aims to understand the overall effect of selloffs on shareholder wealth as well as the impact of important influencing factors. Design/methodology/approach - This study is part of capital market studies which investigate shareholder wealth effects (abnormal returns) using event study methodology. To determine the significance of abnormal returns, a standardized cross-sectional test as suggested by Boehmer et al. (1991) was applied. The sample consists of 393 selloffs of publicly traded companies with a deal value of at least EUR 10m. Findings - The findings confirm the overall positive impact of selloffs on shareholder wealth. The average abnormal return on the announcement day of the sample companies amounts to 1.33%. The type of buyer, the relative size of the transaction as well as the financial situation of the seller in particular seem to influence abnormal returns positively. Originality/value - This study investigates shareholder wealth creation through selloffs in the DACH region, a largely neglected region in divestiture research, but now very relevant due to increasing pressure of active foreign investors. Sophisticated statistical methods were used to generate robust findings, which are in line with the results of similar studies for the US and the UK.
Keywords: 650; Abnormal return; DACH region; Divestitures; Event study methodology; Selloffs; Shareholder wealth